Exploring Education Beyond the Classroom: Experiences From the Malaysia-Indonesia Student Exchange - Mohd Ali, Nor Aishah; Abu Bakar, Siti Anis Nadia; Sapari, Afidah; Bani, Hamidah; Ibrahim, Sharifah Norhafiza; Nurlaila; Harmain, Hendra (Information Management and Business Review, 2024)
Student outbound activities offer unique opportunities for experiential learning beyond the traditional classroom setting. These activities, ranging from international exchanges to community projects, are instrumental in developing students’ key skills such as cultural awareness, adaptability, and global citizenship. They foster a firsthand approach to education, encouraging students to engage with diverse environments and challenges, thereby enhancing their academic and personal growth in real-world contexts. This study explores the perceptions and experiences of students participating in a four-day academic exchange outbound program between the Faculty of Accountancy at Universiti Teknologi MARA (UiTM), Malaysia, and the State Islamic University of North Sumatera Medan (UiNSU), Indonesia. Engaging 14 students with bachelor’s in accountancy, five lecturers from Malaysia, and 40 students with 18 lecturers from Indonesia, the program encompassed community service, innovation projects, and cultural activities. These activities aimed to enhance cultural understanding, academic collaboration, and a platform for experiential learning, crucial in today’s increasingly interconnected world. The study employs a mixed-method approach, utilizing questionnaires and interviews, to explore students’ perceptions of short-term inter-country academic exchanges. The results of the independent t-test indicate no significant differences between the perception of respondents from UiTM and UiNSU in both categories assessed, community service and innovation competition. Additionally, outbound activities contribute to students’ educational and personal development, fostering community service and encouraging cross-cultural interaction through innovation competition. The study highlights the potential of short-duration academic trips to educational contexts in Southeast Asia, underscoring their importance in enhancing the global readiness of university students